Model and characterization for dynamic non-uniform pixel capacitance in electrowetting displays - Shufa Lai; Diguo Zhai; Taiyuan Zhang; Linwei Liu; Zichuan Yi; Dong Yuan; Biao Tang; Guofu Zhou (Results in Physics, 2023)
Electrowetting display (EWD) is a new reflective display device that has the advantages of fast response speed, low power consumption, and video playback. The pixel capacitance of EWDs changes with the flow of internal liquid during the pixel-on process, which affects the pixel response speed. To characterize the change in pixel capacitance and analyze the relationship between pixel capacitance and pixel response speed, we established a dynamic capacitance model during the pixel-on process, derived the integral equation of pixel capacitance, and demonstrated the validity of the model. Meanwhile, we also investigated the effects of the initial angle formed between the oil and the pixel wall, and the relative permittivity of the oil and the hydrophobic insulating layer on the pixel capacitance, respectively. Results showed that the pixel capacitance increased as the initial angle and the relative permittivity of the oil and hydrophobic insulation layers increased. In addition, when the initial angle is 0. 4π and the aperture ratio exceeded 30%, the time required for the pixel to reach the corresponding aperture ratio was the shortest. Moreover, the smaller the relative permittivity of hydrophobic insulating layer, the shorter time required for the pixel to reach the corresponding aperture ratio.